2000
DOI: 10.1046/j.1471-4159.2000.0750840.x
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Increased Oxidative Damage to Lipids, Proteins, or DNA in Huntington's Disease

Abstract: It has been proposed that mitochondrial dysfunction and excitotoxic mechanisms lead to oxidative damage in the brain of Huntington;s disease patients. We sought evidence that increased oxidative damage occurs by examining postmortem brain material from patients who had died with clinically and pathologically diagnosed Huntington's disease. Oxidative damage was measured using methods that have already demonstrated the presence of increased oxidative damage in Parkinson's disease, Alzheimer's disease, and senile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Similarly, there was not an increased level of protein carbonyls in these tissues [129]. Several studies, however, have shown DNA strand breaks in HD post-mortem tissue as detected by in situ end labeling of DNA.…”
Section: Huntington's Diseasementioning
confidence: 70%
“…Similarly, there was not an increased level of protein carbonyls in these tissues [129]. Several studies, however, have shown DNA strand breaks in HD post-mortem tissue as detected by in situ end labeling of DNA.…”
Section: Huntington's Diseasementioning
confidence: 70%
“…Studies in cancer have proposed 8-oxoGua as a potential biomarker, with the supporting evidence that GC to TA transversions (potentially from 8-oxoGua lesions) have been observed within the ras and p53 genes in liver and lung cancers (Cooke et al, 2003; Hussain et al; Rodin and Rodin, 2005). Although oxidative stress has been implicated in neurological disorders such as AD (Gabbita et al, 1998; Lovell et al, 1999; Lyras et al, 1997; Mecocci et al, 1994; Wang et al, 2005), PD (Alam et al, 1997; Nakabeppu et al, 2007; Zhang et al, 1999), and Huntington's disease (De Luca et al, 2008), it has been difficult to assess the level or determine the direct role of DNA oxidative lesions in these disorders (Alam et al, 2000; Te Koppele et al, 1996). Studies have examined levels of 8-oxoGua relating to cardiovascular disease and found increased levels of 8-oxoGua and 8-oxodG lesions in atherosclerotic plaques (De Flora et al, 1997; Martinet et al, 2002), and one study reported a strong association between increased levels of 8-oxodG and premature coronary artery disease in men (Collins et al, 1998a).…”
Section: Dna Oxidative Lesions As a Measure Of Oxidant Stressmentioning
confidence: 99%
“…Several biomarkers of oxidative stress including lipid peroxidation, nucleic acid and protein oxidation byproducts, are increased in HD brains (Browne et al, 2006; Browne et al, 1997; Chen et al, 2007; Hersch et al, 2006; Klepac et al, 2007; Polidori et al, 1999; Sorolla et al, 2008; Sorolla et al, 2010). However, there are some studies that have failed to detect any sign of oxidative damage in HD brains (Alam et al, 2000). Despite its ubiquitous expression, mutant HTT (mtHtt) selectively affects medium spiny striatal neurons, and oxidative stress together with mitochondrial dysfunction have been implicated in the pathology of HD (Bano et al, 2011).…”
Section: Oxidative Stress and Neuronal Cell Deathmentioning
confidence: 99%